The benefits and risks of CTLA4 inhibitor plus PD1/PDL1 inhibitor in stage IIIB/IV non‐small cell lung cancer: A systematic analysis and meta‐analysis based on randomized controlled trials. (8th June 2021) - Liu, Qiangyun; Fang, Zige; Liu, Miaowen; Xu, Ruoxin; Yi, Fengming; Wei, Yiping; Zeng, Linxiang; Zhang, Wenxiong
Abstract: What is known and objective: Although immune checkpoint inhibitors (ICIs) have shown clinical benefit for patients with non‐small cell lung cancer (NSCLC), the efficacy of the combination of ICIs targeting different pathways is still unclear. We performed this meta‐analysis to explore the efficacy of cytotoxic T‐lymphocyte‐associated protein 4 (CTLA‐4) inhibitor plus programmed cell death 1 receptor (PD‐1)/programmed cell death receptor ligand 1 (PD‐L1) inhibitor therapy (CP) for NSCLC IIIB/IV patients. Methods: We systematically searched the main databases for relevant studies. The main outcomes were overall survival (OS) and progression‐free survival (PFS). Results and discussion: We identified 3526 articles, including 5 randomized controlled trials (RCTs) (4377 patients), in our meta‐analysis. We conducted two comparisons of CP versus chemotherapy or PD1/PDL1 inhibitor (P). Compared with chemotherapy, CP was more effective, with better OS (hazard ratio [HR]: 0.77, 95% CI [confidence interval]: 0.66–0.91; p = 0.001), better PFS (HR: 0.77, 95% CI: 0.70–0.85; p < 0.00001) and comparable objective response rate (ORR) (risk ratio [RR]: 1.27, 95% CI: 0.98–1.65; p = 0.07); in terms of toxicity, CP was comparable to chemotherapy across all‐grade adverse events (AEs) (RR: 0.87, 95% CI: 0.73–1.03; p = 0.11) and grade 3–5 AEs (RR: 0.85, 95% CI: 0.63–1.14; p = 0.27). Compared with P, CP had no superiority in efficacy in terms of the OS (HR: 1.04, 95%CI: 0.86–1.24; p =0.70), PFS (HR: 0.95, 95%CI: 0.75–1.22; p = 0.70) and the ORR (RR: 1.07, 95% CI: 0.95–1.21; p = 0.27) but CP was more effective than P when PD‐L1 expression was <1% (RR: 0.77, 95%CI: 0.60–0.98; p = 0.04); in terms of toxicity, CP was associated with increased all‐grade AEs (RR:1.07, 95% CI: 0.97–1.19; p = 0.18) and grade 3–5 AEs (RR:1.58, 95% CI: 1.21–2.07; p = 0.0008). What is new and conclusion: CP is a beneficial therapeutic schedule with longer PFS and OS than chemotherapy and has an acceptable, manageable grade 3–4 AE rate in IIIB/IV NSCLC. However, compared with P, CP results in better OS only in patients with PD‐L1 expression <1%. Abstract : CP is a beneficial therapeutic schedule with longer PFS and OS than chemotherapy in IIIB/IV NSCLC. However, compared with P, CP results in better OS only in patients with PD‐L1 expression <1%.